2008
DOI: 10.1016/j.compscitech.2008.09.011
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of particle size on fracture toughness of polymer composites

Abstract: Fracture toughness of particle reinforced polymers is strongly affected by the size of particles. It can be improved or reduced depending on the materials used and the volume fractions at which the values are compared. Dissipation mechanisms, as particle debonding and subsequent yielding of the polymer, are responsible for the characteristic behaviour. If the debonding energy per volume is considered it can be concluded that smaller particles are favourable for this value. But the product of the specific debon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(41 citation statements)
references
References 22 publications
1
40
0
Order By: Relevance
“…Composites that had a low aspect ratio showed superior strength, which allows better transfer between the matrix and the fillers (Ashori and Nourbakhsh 2009). Moreover, some researchers concluded on the basis of an energy debonding criterion damage dissipation is strongly dependent on the size of particles, where smaller particles are favorable to increase material toughness (Lauke 2009). Meanwhile, at the same particle content, smaller particle size leads to lower interparticle distance where extensive plastic deformation in the matrix can be easily induced (Zhang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Composites that had a low aspect ratio showed superior strength, which allows better transfer between the matrix and the fillers (Ashori and Nourbakhsh 2009). Moreover, some researchers concluded on the basis of an energy debonding criterion damage dissipation is strongly dependent on the size of particles, where smaller particles are favorable to increase material toughness (Lauke 2009). Meanwhile, at the same particle content, smaller particle size leads to lower interparticle distance where extensive plastic deformation in the matrix can be easily induced (Zhang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the Izod impact test data cannot be used for design purposes, although they can be used for comparing the toughness between different polymer systems. With the objective to characterize toughness of polymer nanocomposites with greater accuracy, many researchers have adopted fracture mechanics approach in their studies [2,16,17]. Furthermore, the toughness evaluation of PA6/PP/ elastomer nanocomposites, particularly fracture toughness, has not been systematically investigated.…”
mentioning
confidence: 99%
“…Since this research intends to reach the best combination to improve the ductility of the adhesive, it can be concluded that the small particles are the best option in case of tensile loading. Several authors have studied the effect of particle size on the mechanical performance of thermosetting polymers [20,32,33]. Some studies [19,34] indicate that, for composites with micro scale particles, fracture toughness generally increases with particle size, but this analysis is not consensual.…”
Section: Analysis Of Maximum Strain Results-analysis Of Variance and mentioning
confidence: 99%